2021
DOI: 10.3390/app11188603
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Bioactive Plant Volatiles for the Carob Moth by Means of GC-EAD and GC-Orbitrap MS

Abstract: The aim of this study was to validate a workflow that allows structural identification of plant volatiles that induce a behavioral response in insects. Due to the complexity of plant volatile emissions and the low levels at which these bioactive components tend to occur, gas chromatography-electroantennography (GC-EAD) was applied as the prime differentiator technique, i.e., to indicate particular peaks of interest in the chromatogram. In a next step, the analysis was repeated under identical conditions using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…Among the olfactively active compounds, behavioral experiments showed that β-caryophyllene had an attractive pre-contact effect on D. radicum females, which supports an important role of this compound in plant-insect interactions as it has been shown attractive to a diversity of generalist and specialist phytophagous insects (e.g. [70][71][72]). However, it is the only VOC which induced pre-or post-contact effect when applied alone, while all three VOC mixtures had such effect.…”
Section: Discussionmentioning
confidence: 90%
“…Among the olfactively active compounds, behavioral experiments showed that β-caryophyllene had an attractive pre-contact effect on D. radicum females, which supports an important role of this compound in plant-insect interactions as it has been shown attractive to a diversity of generalist and specialist phytophagous insects (e.g. [70][71][72]). However, it is the only VOC which induced pre-or post-contact effect when applied alone, while all three VOC mixtures had such effect.…”
Section: Discussionmentioning
confidence: 90%
“…The collaboration between chemists and biologists, and the introduction of newer analytical techniques, enabled the development of additional approximations to pheromone research or bioactive compounds characterization by untargeted metabolomics (Butcher, 2017;Hefetz, 2019;Li et al, 2018). Most of the studies have focused on the volatile pheromones of different organisms and the employment of GC-MS or GC-HRMS instruments to this aim: in yeast (Ljunggren et al, 2019), insects (Esteves et al, 2017) and plants (Hosseini et al, 2021;Zheng et al, 2021). For more polar pheromones, LC-HRMS was used in marine planktonic diatoms (Fiorini et al, 2020) and nematodes (Falcke et al, 2018;Le et al, 2020),…”
Section: Introductionmentioning
confidence: 99%